Ética utilitarista: problemas e respostas - Araújo, Leandro Shigueo (2015)
The philosophical ethics deals with related issues to the meaning of the speech and moral practices, the criterion of right and wrong, good and bad and applications of this in solving problems. Utilitarianism is an ethical theory which helps us to solve moral problems, by means of the calculation of utilities that involve action, rules and moral institutions. Therefore, it is important to analyze the referred theory as way of knowing if there are good reasons to accept the recommendations that it offers, regarding the resolution of moral problems. In this work, we intend to analyze the ethical theory named Utilitarianism. It will be explained its main characteristics in detail, such as the consequentialism and the welfarism, and how they organize the whole basis of the theory. Moreover, we aim to verify how those characteristics are strongly criticized by various objections, among which some are very important, since they cause problems to the theory. Also, it will be explained the respective responses which utilitarians developed in order to answer the objections, even if it meant to alter some theoretical aspects. In addition, we will analyze the objections directed to Utilitarianism in general, such as those which claim that the theory violates the rights of people and their sense of justice. In this way, we intend to discuss if Utilitarianism is a satisfactory ethical theory or not, and after the research, we think it is.